A Description of Pocobletus Coroniger Simon (Araneae, Linyphiidae) - Arthur M. Chickering (Psyche: A Journal of Entomology)
More than thirty years ago I began finding this species in my coIlections from localities in the Panama Canal Zone. For many years they were regarded as representatives of a new genus. During a period of work in the Museum National d'Histoire Naturelle in Paris in 958 Dr. H. W. Levi made sketches of the type specimens of Pocobletus coroniger Simon and later identified my specimens from Panama. In I894 Simon gave a brief definition of the genus Pocobletus and in a footnote he gave a very brief description of both sexes of Pocobletus coroniger and included the species in his general treatment of the Argiopidae. No figures were given with the description. Because of the uncertainties regarding the status of the species it now seems worth while to prepare a series of figures together with what I hope will be regarded as an adequate description of both sexes of this interesting species. As a basis for this description I have selected a male from Summit, Panama Canal Zone, August, I950 and a female from Barro Colorado Island, Canal Zone, February, I958. Other specimens from localities in the Canal Zone have also been used to supplement data derived from these two specimens.